Economic integration, market power and technological change - Tapio Palokangas (Institute for the Study of Labor (IZA), 2005)
We examine a common market which expands by integrating new regions. Capitalists are strategically interdependent through the goods market and they improve their productivity through R&D. Production and R&D employ unionized workers. The purpose of integration is to maximize a weighed average of workers' and capitalists' utilities. The main findings are as follows. Integration benefits capitalists more than workers. If labour unions are strong enough, then the common market can expand indefinitely. Otherwise, there is an upper limit for integration. This is the higher, the higher producer market power or the stronger the capitalists' political influence.
Keywords: F15; J50; O40; 330; economic integration; market power; endogenous growth